Threads of Diversity: Weaving Cultures in Thrity Umrigar’s The Story Hour (International Journal of Food and Nutritional Sciences, 2022)
Cultural pluralism is a situation in which a minority group maintains its distinct culture while participating in a society with a separate, dominant culture. Umrigar presented this cultural pluralism through herprotagonist Lakshmi in the novel The Story Hour. Lakshmi, an immigrant woman who follows all the Indian traditional valuesin her settled country America. Lakshmi represented people who migrated due to various reasons but they always bound with their values and culture.